Anaesthesia bootcamp 2024: primary examination edition I (written) - Samsudin, Afifah; Ahmad, Fauziah (Faculty of Medicine, 2024)
This was the first of a two-part Anaesthesia Bootcamp series, with the second part focused on the viva voce (oral) component of the exam, held in March 2024. Building on the success of previous internal mock exams, this year's Anaesthesia Bootcamp was expanded to a larger scale, benefiting participants from outside of UiTM. The program drew in 96 anaesthesia postgraduate students from UiTM and other healthcare institutions nationwide.